PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, PERSENTASE PENAWARAN SAHAM, UMUR PERUSAHAAN, REPUTASI PENJAMIN, REPUTASI AUDITOR TERHADAP INITIAL RETURN - Imang Dapit Pamungkas (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
The  capital  market  is  a  source  of  business  financing  and  investment  alternatives  in  the  securities sector. There are some anomalies that occur when the stock traded in the secondary market. When stock prices in the secondary market is higher than the stock price on the primary market, and there was a positive initial return (underpricing), the inverse is negative initial return (overpricing). The purpose  of  this  study  was  to  determine  the  influence  is  there  any  financial  information  and  non- financial  to  the  initial  return  on  the  IPO  companies  listed  in  Indonesia  Stock  Exchange.  The population in this study is a company doing an IPO and listed on the Stock Exchange. Samples were taken  using  purposive  sampling  method  on  the  company's  IPO  in  2008-2010.  Method  of  data collection  methods  documentation.  This  study  uses  descriptive  analysis  and  multiple  regression analysis.The  results  showed  that  the  financial  information  for  the  company  size,  profitability influential and non-financial information significant effect on initial returns. Suggestions that can further research is recommended to (1) further research better add factors outside the company in research, (2) adding further researcher financial information and non-financial information.  Keywords:  Company  Size,  Profitability,  Financial  Leverage,  Corporate  Age,  Auditor  Reputation, Reputation    Underwriters and Initial Return